HAM dalam bingkai pembangunan dan demokrasi - Sudjana, Eggi; Husein, Ali Sofwan; Center for Information and Development Studies (Indonesia) (Jakarta, Indonesia : CIDES, 1997)
Human rights in Indonesia ; collection of articles
Includes bibliographical references
Keywords: Human rights -- Indonesia; Democracy -- Indonesia